Pengaruh kinerja petugas kesehatan pada tingkat kepuasan pasien - Muhammad Nurhidayat; M. Arifki Zainaro (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
The performance of health workers and patient satisfaction Background: Patient satisfaction related to the quality of health services by knowing the level of patient satisfaction, puskesmas can improve service quality. The percentage of patients who expressed satisfaction with the service based on the results of the survey with standard instruments. HR performance is a term derived from the word Job Performance or Actual Performance (work performance or actual achievement achieved by someone)Purpose: To determine the effect of the performance of health workers on patient satisfaction in Public health centers.Method: A quantitative with the design correlative. The population were patients who were inpatient at 7 Public Health Centers in West Lampung District, with a total sample of 130 respondents. Sampling in this study using the Cluster Sampling method (Sample Area)Results: Most respondents rated the performance of health workers in the poor category of 78 respondents (60.0%) and the majority of respondents were dissatisfied numbered 69 respondents (53.1%). Based on the results of statistical tests, p-value 0.034 or p-value <α (0.05) is obtained, which means there is a relationship between health worker performance and patient satisfaction.Conclusion: The results of this study are expected that the Public health centre management can improve the performance of nurses and can develop or update the best quality of service for patients, by providing facilities, facilities and infrastructure to support health services, improve all quality service procedures and improve performance related programs, and by improving health status, so that patient satisfaction can be improved.Keywords: The performance; Health workers; Patient satisfaction Pendahuluan : Kepuasan pasien yang berhubungan dengan mutu pelayanan kesehatan dengan mengetahui tingkat kepuasan pasien, puskesmas dapat meningkatkan mutu pelayanan. Persentasi pasien yang menyatakan puas terhadap pelayanan berdasarkan hasil survey dengan instrument yang baku. Kinerja SDM merupakan istilah yang berasal dari kata Job Performance atau Actual Performance (prestasi kerja atau prestasi sesungguhnya yang dicapai seseorang)Tujuan : Diketahui pengaruh kinerja petugas kesehatan terhadap kepuasan pasien Di Puskesmas Se-Kabupaten Lampung Barat Tahun 2019.Metode : Kuantitatif dengan desain yang digunakan dalam penelitian ini adalah korelatif. Populasi dalam penelitian ini adalah pasien yang datang berobat/dirawat pada Puskesmas Se-Kabupaten Lampung Barat, dengan jumlah sampel di 7 Puskesmas berjumlah 130 responden. Pengambilan sampel dalam penelitian ini menggunakan metode Cluster Sampling (Area Sampel)Hasil : Sebagian besar responden menilai kinerja petugas kesehatan dalam kategori buruk berjumlah 78 responden (60,0%) dan sebagian besar responden merasa tidak puas berjumlah 69 responden (53,1%). Berdasarkan hasil uji statistik, didapatkan p-value 0,034 atau p-value < nilai α (0,05) yang artinya terdapat hubungan antara kinerja petugas kesehatan dengan kepuasan pasien.Simpulan: Hasil penelitian ini diharapkan agar pihak Puskesmas dapat meningkatkan kinerja perawat dan dapat mengembangkan atau memperbaharui kualitas pelayanan yang terbaik untuk pasien, dengan cara menyediakan fasilitas, sarana dan prasarana dalam menunjang pelayanan kesehatan, memperbaiki semua tatacara pelayanan yang bermutu serta meningkatkan program kinerja yang berhubungan dengan peningkatan status kesehatan, sehingga kepuasan pasien dapat ditingkatkan.